2016
DOI: 10.1002/14651858.cd011058.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-mediated exercises for improving outcomes after stroke

Abstract: There is very low- to moderate-quality evidence that CME may be a valuable intervention to augment the pallet of therapeutic options for stroke rehabilitation. Included studies were small, heterogeneous, and some trials had an unclear or high risk of bias. Future high-quality research should determine whether CME interventions are (cost-)effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 134 publications
4
46
1
7
Order By: Relevance
“…Other reviews in this category did not report the specific studies that were used, including three that reported backward citation searching [42][43][44] and three that reported forward citation searching. 28,29,39 Included studies were used for backward citation searching in 94 of 159 (59%) reviews and forward citation searching in eight of 15 (53%) reviews that reported the set of studies used. Included studies are by convention listed in full in a Cochrane review.…”
Section: What Sets Of Studies Are Used and How Frequently?mentioning
confidence: 99%
See 1 more Smart Citation
“…Other reviews in this category did not report the specific studies that were used, including three that reported backward citation searching [42][43][44] and three that reported forward citation searching. 28,29,39 Included studies were used for backward citation searching in 94 of 159 (59%) reviews and forward citation searching in eight of 15 (53%) reviews that reported the set of studies used. Included studies are by convention listed in full in a Cochrane review.…”
Section: What Sets Of Studies Are Used and How Frequently?mentioning
confidence: 99%
“…Of the 18 Cochrane reviews that reported using a citation index to conduct citation searching, 15 (83%) reported the name of the citation index(es) used. Google Scholar was reported in one review 55 ; Scopus was reported in two reviews 24,29 ; and Web of Science was reported in 13 reviews, [26][27][28][29]31,32,[34][35][36][37][38][39][40] including seven reviews [26][27][28][29]32,34,39 that reported searching the Science Citation Index (a subset of the Web of Science) in particular and one review 35 that reported searching the Core Collection (which includes the Social Sciences Citation Index and Arts & Humanities Citation Index) in particular.…”
Section: What Citation Indexes Are Used and How Frequently?mentioning
confidence: 99%
“…Caregiver‐ or family‐mediated exercises (CMEs; Galvin, Cusack, O'Grady, Murphy, & Stokes, 2011; van den Berg et al, 2016; Vloothuis et al, 2015; Vloothuis et al, 2016), in which caregivers, such as partners, family members, or friends are actively involved in rehabilitation training, may be a promising and cost‐effective way to augment intensity of daily practice during inpatient stay. CME can continue after discharge to a patient's own home situation and thereby facilitate ESD.…”
Section: Introductionmentioning
confidence: 99%
“…CME can continue after discharge to a patient's own home situation and thereby facilitate ESD. A systematic review of nine trials found very low to moderate quality evidence that CME can improve standing balance, walking distance, and quality of life, without increasing caregiver burden, suggesting that CME may augment the pallet of therapeutic options for rehabilitation after stroke (Vloothuis et al, 2016). However, none of these trials included e‐health technology such as telerehabilitation services to support treatment adherence or included exercise apps to support CME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation